Dye-sensitized solar cell

By optimizing the cell size in the current direction to 6-10 mm in dye-sensitized solar cells, the peeling stress caused by thermal expansion is minimized, enhancing durability and maintaining high fill factor performance.

JP2025082141APending Publication Date: 2025-05-28TOPPAN HOLDINGS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023195415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-11-16
Publication Date
2025-05-28

AI Technical Summary

Technical Problem

In Z-type dye-sensitized solar cell modules, peeling stress generated by thermal expansion of the electrolytic solution can lead to poor conductivity due to its impact on conductive particles in the sealing material, resulting in reduced durability.

Method used

The dye-sensitized solar cell design includes a sealing material with conductive particles between substrates, where the cell size in the current direction is optimized to be between 6 mm and 10 mm to minimize peeling stress and ensure effective conductivity.

Benefits of technology

This configuration enhances the durability of the dye-sensitized solar cells by reducing peeling stress and maintaining high fill factor performance, even under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025082141000001_ABST
    Figure 2025082141000001_ABST
Patent Text Reader

Abstract

To provide a dye-sensitized solar cell with high durability.SOLUTION: A dye-sensitized solar cell includes a plurality of units of dye-sensitized solar cells including an electrode, an electron transport layer, a light absorption layer, a counter electrode, a catalyst layer, an electrolyte solution, and a sealing material. The electrode is formed on a first substrate. The electron transport layer is formed on the electrode. The light absorption layer is formed on the electron transport layer and includes an electron capture agent and a dye. The counter electrode is formed on a second substrate disposed facing the first substrate. The catalyst layer is formed on the counter electrode. The electrolyte solution fills a space between the light absorption layer and the catalyst layer. The sealing material is held between the first substrate and the second substrate, and seals the electrode, the electron transport layer, the light absorption layer, the counter electrode, the catalyst layer, and the electrolyte solution. A region surrounded by an inner wall of the sealing material forms one power generation element. The size of each power generation element in a direction of current flowing in the unit is 6 mm or more and 10 mm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a dye-sensitized solar cell.

Background Art

[0002] Solar cells are expected to be power sources and energy harvesting elements for IoT (Internet of Things) devices. Solar cells are roughly classified into silicon-based solar cells, compound-based solar cells, and organic-based solar cells. Among organic-based solar cells, dye-sensitized solar cells (DSCs) are known. Dye-sensitized solar cells generate electricity through a redox reaction using a dye for absorbing light and an electrolyte. The electrolytes used in dye-sensitized solar cells include solid electrolytes and liquid electrolytes.

[0003] Dye-sensitized solar cells may be used as modules in which units of a plurality of dye-sensitized solar cells are connected in series to increase the light-receiving area. Here, in order to connect a plurality of units in series, electrodes provided in each unit may be conductively connected vertically using a sealing material mixed with conductive particles. A solar cell module having such a structure may be called a Z-type module.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] In a Z-shaped module, peeling stress is generated in the sealing material of the upper and lower conduction connection parts due to the influence of the thermal expansion of the electrolytic solution caused by temperature rise. When this peeling stress acts on the conductive particles mixed in the sealing material, it may lead to poor conductivity. There is a demand for a dye-sensitized solar cell having high durability in which the influence on the conductive particles due to the peeling stress of such a sealing material hardly occurs.

[0006] An object of the present disclosure is to provide a dye-sensitized solar cell having high durability.

Means for Solving the Problems

[0007] A dye-sensitized solar cell according to one aspect includes a plurality of units of a dye-sensitized solar cell including an electrode, an electron transport layer, a light absorption layer, a counter electrode, a catalyst layer, an electrolytic solution, and a sealing material. The electrode is formed on a first substrate. The electron transport layer is formed on the electrode. The light absorption layer is formed on the electron transport layer and contains an electron collector and a dye. The counter electrode is formed on a second substrate disposed opposite to the first substrate. The catalyst layer is formed on the counter electrode. The electrolytic solution is filled between the light absorption layer and the catalyst layer. The sealing material is interposed between the first substrate and the second substrate and seals the electrode, the electron transport layer, the light absorption layer, the counter electrode, the catalyst layer, and the electrolytic solution. The region surrounded by the inner wall of the sealing material of each unit constitutes one power generation element. The size in the current direction flowing through the unit of each power generation element is 6 mm or more and 10 mm or less.

Effects of the Invention

[0008] According to the present disclosure, a method for manufacturing a dye-sensitized solar cell having high durability can be provided.

Brief Description of the Drawings

[0009]

Figure 1

Figure 2

Figure 3

Figure 4

Figure 5

Figure 6

Figure 7

Figure 8

Figure 9

Figure 10

Figure 11

DETAILED DESCRIPTION OF THE INVENTION

[0010] Hereinafter, embodiments will be described with reference to the drawings. FIG. 1 is a diagram showing an example of the configuration of a dye-sensitized solar cell according to an embodiment. The dye-sensitized solar cell 1 in FIG. 1 is a dye-sensitized solar cell module having a Z-type structure in which a plurality of units U1, U2, U3, U4 of dye-sensitized solar cells are connected in series. In FIG. 1, the number of units is 4. The number of units is not limited to 4.

[0011] As shown in FIG. 1, each of the units U1, U2, U3, and U4 of the dye-sensitized solar cell 1 is formed between a first substrate 11 and a second substrate 12. The first substrate 11 is a transparent substrate such as a glass substrate. The second substrate 12 is arranged to face the first substrate 11. The second substrate 12 is a transparent substrate such as a glass substrate, similar to the first substrate 11.

[0012] An electrode 13 is formed at the position of each unit of the first substrate 11. The interval between the electrodes 13 is, for example, an interval such that there is no influence such as leakage current between adjacent electrodes. The electrode 13 is formed of a transparent conductive oxide film (TCO) such as indium tin oxide (ITO) or fluorine-doped tin oxide (FTO). Each electrode 13 is used as the anode electrode of the corresponding unit. Also, of the units U1 and U4 which are the end units in the dye-sensitized solar cell 1, one unit, the electrode 13 formed in the unit U4 in FIG. 1, is drawn out to the outside of the dye-sensitized solar cell 1. The electrode 13 drawn out to the outside is connected to the counter electrode 14 via the vertical conduction sealing material 19. This counter electrode 14 is drawn out to the outside of the dye-sensitized solar cell 1. A terminal 131 is formed on the drawn-out counter electrode 14. A wiring is drawn out from the terminal 131. This wiring is connected to one end of a load (not shown). The terminal 131 may be formed on the electrode 13 drawn out to the outside.

[0013] At the position of each unit of the second substrate 12, a counter electrode 14 is formed. The interval between the counter electrodes 14 is, for example, an interval such that there is no influence such as leakage current between adjacent electrodes. The counter electrode 14 is formed of a transparent conductive oxide film (TCO) such as indium tin oxide (ITO) or fluorine-doped tin oxide (FTO), similar to the electrode 13. Each counter electrode 14 is used as the cathode electrode of the corresponding unit. Also, of the units U1 and U4 which are the end units in the dye-sensitized solar cell 1, the counter electrode 14 formed in the unit U1 in FIG. 1 is drawn out to the outside of the dye-sensitized solar cell 1. A terminal 141 is formed on the drawn-out counter electrode 14. Wiring is drawn out from the terminal 141. This wiring is connected to the other end of a load (not shown). The terminal 141 may be formed on the side of the first substrate 11 by using an upper and lower conduction sealing material 19.

[0014] An electron transport layer 15 is formed on the electrode 13 that constitutes the anode electrode of each unit. The electron transport layer 15 is composed of a metal oxide film of titanium oxide (TiO x )). The electron transport layer 15 can be provided to suppress the loss caused by the electrode 13 composed of a TCO having a higher resistance than that of a metal. Also, by forming the electron transport layer 15, the adhesion of the light absorption layer 16 further formed on the electron transport layer 15 is improved. As shown in FIG. 1, the electron transport layer 15 may be formed integrally with the electrode 13. In this case, similar to the electrode 13 in the unit U4, the electron transport layer 15 in the unit U4 may also be drawn out to the outside of the dye-sensitized solar cell 1.

[0015] A light absorption layer 16 is formed on each electron transport layer 15. The light absorption layer 16 is a layer formed by adsorbing a dye on an electron collector. The electron collector is, for example, a minute oxide semiconductor, for example, titanium oxide (TiO 2) is an integrated body. The dye is, for example, a ruthenium (Ru) dye (RU) (such as N719 dye). The electron collector is not limited to titanium oxide, and may be, for example, zinc oxide, tin oxide, tungsten oxide, niobium oxide, indium oxide, and their composites. Also, the dye is not limited to N719 dye. For example, as ruthenium-based dyes, N3 dye, BlackDye, and as pure organic dyes, D149, xanthene, PVK, merocyanine, oxazine, etc. may be used.

[0016] A catalyst layer 17 is formed on the counter electrode 14 that constitutes the cathode electrode of each unit. The catalyst layer 17 is, for example, a platinum layer. The catalyst layer 17 may be formed integrally with the counter electrode 14. In this case, similar to the counter electrode 14 in the unit U1, the catalyst layer 17 in the unit U1 may also be drawn out to the outside of the dye-sensitized solar cell 1.

[0017] An electrolytic solution 18 is filled between the light absorption layer 16 and the catalyst layer 17 of each unit. As the solvent of the electrolytic solution 18, for example, acetonitrile, methoxyacetonitrile, ethylene carbonate, etc. can be used. As the solute of the electrolytic solution 18, for example, iodine (I 2) 1,2-dimethyl-3-n-propylimidazolium iodide (DMPImI), lithium iodide (LiI), 4-tert-butylpyridine (TBP), etc. can be used. As shown in FIG. 1, the electrolytic solution 18 is partitioned by upper and lower conduction sealants 19 provided at the boundary positions between the respective units U1 and U2, between the unit U2 and the unit U3, and between the unit U3 and the unit U4. The upper and lower conduction sealants 19 are constituted by containing a conductive material containing conductive particles in a resin excellent in solvent resistance such as an acrylic resin and an olefin resin. The conductive particles also function as spacers for maintaining the gap between the first substrate 11 and the second substrate 12 at a predetermined value. The upper and lower conduction sealants 19 bond the first substrate 11 and the second substrate 12 together and are provided between the opposing electrodes to conduct between the units. That is, the upper and lower conduction sealant 19 provided at the boundary position between the unit U1 and the unit U2 conducts the electrode 13 of the unit U1 and the opposing electrode 14 of the unit U2. The upper and lower conduction sealant 19 provided at the boundary position between the unit U2 and the unit U3 conducts the electrode 13 of the unit U2 and the opposing electrode 14 of the unit U3 through the electron transport layer 15 and the catalyst layer 17. The upper and lower conduction sealant 19 provided at the boundary position between the unit U3 and the unit U4 conducts the electrode 13 of the unit U3 and the opposing electrode 14 of the unit U4. Thereby, the units U1, U2, U3, and U4 are connected in series.

[0018] An external sealant 20 is formed between the electron transport layer 15 and the catalyst layer 17 at the outermost peripheral portion of the dye-sensitized solar cell 1. The external sealant 20 bonds the first substrate 11 and the second substrate 12 together and prevents the electrolytic solution 18 from leaking to the outside. That is, the electrolytic solution 18 is sealed by the first substrate 11, the second substrate 12, the upper and lower conduction sealants 19, and the external sealant 20. The external sealant 20 is, for example, a resin. Note that the upper and lower conduction sealant 19 is provided at the portion where the terminal 131 is formed in the external sealant 20. Thereby, the electrode 13 and the opposing electrode 14 are conducted, and the terminal 131 can be formed on the side of the second substrate 12.

[0019] Figure 2 is a plan view of the dye-sensitized solar cell 1 as seen from the side of the first substrate 11. In the embodiment, the region surrounded by the inner walls of the upper and lower conduction sealing materials 19 and the outer sealing material 20 of each unit constitutes the cell in each unit. The cell is a power generation element that contributes to power generation in each unit. In Figure 2, one cell is shown as EL. In the following description, it is assumed that the size along the direction of the current flowing through each unit is A, and the size along the direction orthogonal to the direction of the current is B. For example, in the case of the dye-sensitized solar cell 1 having the configuration shown in Figure 1, the current flows along the arrangement direction of the units. Therefore, in the case of the configuration of Figure 1, the direction of the current flow is the short side direction of the cell. In this case, as shown in Figure 2, the size in the short side direction of the cell is A, and the size in the long side direction of the cell is B. Also, the cell area is the product of A and B. Hereinafter, the description will continue with the direction parallel to the short side direction of the cell being the horizontal direction and the direction parallel to the long side direction of the cell being the vertical direction.

[0020] Figure 3 is a diagram for explaining the power generation principle in one unit of the dye-sensitized solar cell. Also, in the following example, it is assumed that the electron collector is titanium oxide (TiO 2 ), the dye is a ruthenium (Ru) dye, and the electrolytic solution 18 is an iodine (I) electrolytic solution.

[0021] First, when light is incident on the dye-sensitized solar cell, the light is absorbed by the dye 16a formed on the substrate. The dye 16a is excited by absorbing the light. The reaction formula is shown, for example, by the following formula (1). Ru→Ru + +e - (1)

[0022] The electrons (e - ) emitted from the excited dye 16a are injected into the electron collector 16b composed of, for example, porous titanium oxide (TiO 2 ). The electrons injected into the electron collector 16b move to the electrode 13 which is the anode electrode.

[0023] On the other hand, the electrons (e- ) The lost dye 16a is supplied with electrons from, for example, iodide ions (I - ) in the electrolyte 18. The iodide ions (I - ) in the electrolyte 18 supply electrons (e - ) to the dye 16a and become triiodide ions (I 3 - ). The reaction equations are shown, for example, by the following equations (2) and (3). Ru + e - → Ru (2) 3I - → I 3 - + 2e - (3)

[0024] The triiodide ions (I 3 - ) generated by such an oxidation reaction attempt to receive electrons (e - ) from the counter electrode 14 which is the cathode electrode. At this time, a potential difference is generated between the counter electrode 14 and the electrode 13. If a load is connected between the counter electrode 14 and the electrode 13, the electrons that have moved to the electrode 13 move through the load to the counter electrode 14. Then, the electrons that have reached the counter electrode 14 are absorbed by the triiodide ions (I 3 - ). By such a reduction reaction, the triiodide ions (I 3 - ) return to iodide ions (I - ). The reaction equation is shown, for example, by the following equation (4). I 3 - + 2e - → 3I - (4)

[0025] By repeating the above oxidation-reduction reaction, the dye-sensitized solar cell 1 generates electricity. For such an oxidation-reduction reaction to occur, the energy level of the excited-state dye 16a needs to be higher than the energy level of the electron collector 16b, and the energy level of the ground-state dye 16a needs to be lower than the energy level of the electrolyte 18.

[0026] FIG. 4 is a diagram showing the I-V characteristics of an example of one unit in a dye-sensitized solar cell. Here, in FIG. 4, the characteristics under illumination of 1 sun (illuminance corresponding to direct sunlight in midsummer. Approximately 100,000 lux) and the characteristics under illumination of 200 lux are shown.

[0027] A fill factor is known as a parameter that can be calculated from the I-V characteristics. The fill factor is calculated from Pmax / (Voc×Isc), where Pmax is the maximum output, Isc is the short-circuit current, and Voc is the open-circuit voltage, obtained from the I-V characteristics. The maximum output Pmax is the output at the point where the product of current and voltage is maximum on the I-V characteristic curve. The short-circuit current Isc is the current when the voltage is zero on the I-V characteristic curve. The open-circuit voltage Voc is the voltage when the current is zero on the I-V characteristic curve.

[0028] Generally, under the conditions of the same short-circuit current Isc and open-circuit voltage Voc, the higher the fill factor of the dye-sensitized solar cell, the greater the maximum output that can be obtained. Generally, the fill factor tends to be high under low illuminance and low under high illuminance. As a factor for the decrease in the fill factor under high illuminance, it can be mentioned that electron recombination in the light absorption layer is more likely to occur under high illuminance than under low illuminance. Thus, since the fill factor also changes depending on the illuminance of the light incident on the dye-sensitized solar cell, it is important to be able to maintain a sufficient fill factor as a dye-sensitized solar cell even when the illuminance changes.

[0029] FIG. 5 is a graph showing the relationship between the cell area and the fill factor. The graph in FIG. 5 shows the fill factor calculated from the I-V characteristics measured in the same manner as in FIG. 4 while changing only the cell area under illumination of 1 sun. Here, the fill factor in FIG. 5 is represented as a ratio when the fill factor when the cell area is 0.06 cm 2 is taken as 1.

[0030] As shown in FIG. 5, under the same illumination, the fill factor tends to decrease as the cell area increases. For example, when the cell area becomes 1 cm 2 , the fill factor decreases by about 20%. Therefore, in order to maintain a high fill factor even under high illuminance, it is desirable that the cell area be small.

[0031] FIG. 6 is a graph showing the relationship between the cell size in the current direction and the fill factor. As described above, in the configuration of FIG. 1, the current direction is the horizontal direction. The graph of FIG. 6 is a graph of the fill factor calculated based on the I-V characteristics measured while fixing the cell area at 1 cm 2 and changing only the horizontal cell size A. Here, the fill factor in FIG. 6 is represented as a ratio when the fill factor when the cell size A is 2.5 mm is set to 1.

[0032] As shown in FIG. 6, at the same cell area, the fill factor tends to decrease as the horizontal cell size A in the current direction increases. And when the cell size A exceeds 10 mm, the decrease amount of the fill factor rapidly increases. Therefore, in order to maintain a high fill factor under the condition of a constant cell area, it is desirable that the horizontal cell size A be 10 mm or less.

[0033] FIG. 7 is a graph showing the relationship between the vertical size ratio and the fill factor. Here, the vertical size ratio B2 / B1 is the ratio of the aspect ratio B1 / A1 when the horizontal cell size A is A1 and the vertical cell size B is B1 and the aspect ratio B2 / A1 when the horizontal cell size A is the same A1 and the vertical cell size is B2. That is, a large vertical size ratio B2 / B1 means that the vertical cell size is made longer with respect to the horizontal cell size. Here, the fill factor in FIG. 7 is represented as a ratio when the fill factor when the vertical size ratio is 1 is set to 1.

[0034] As shown in FIG. 7, at the same horizontal cell size, the fill factor tends to decrease as the vertical size ratio, that is, the vertical cell size B increases. However, the amount of decrease in the fill factor due to the increase in the vertical cell size tends to be less than the amount of decrease in the fill factor due to the increase in the horizontal cell size.

[0035] Here, as described above, it is desirable that the cell area of one cell is small for maintaining the fill factor. On the other hand, in order to obtain the necessary output as the dye-sensitized solar cell 1, a certain light-receiving area is required, and it is desirable that the cell area of one cell is large for expanding the light-receiving area. In order to achieve both of these, it is desirable to reduce the cell area by reducing the horizontal cell size A without changing the vertical cell size B as much as possible. From the results of FIG. 6, a high fill factor is maintained if the cell size is 10 mm or less.

[0036] On the other hand, as the cell size A decreases, peeling stress is likely to occur in the vertical conduction sealing material 19, particularly at high temperatures. Specifically, since the electrolytic solution 18 expands due to the temperature rise, as shown in FIG. 8, pressure is applied inside the power generation element. Here, the four sides of the first substrate 11 and the second substrate 12 are fixed by the vertical conduction sealing material 19 and the external sealing material 20, respectively. Therefore, an evenly distributed load is applied to the first substrate 11 and the second substrate 12. Due to this evenly distributed load, as shown in FIG. 8, the first substrate 11 and the second substrate 12 bend so that the central portion bulges. Due to the bending of the first substrate 11 and the second substrate 12, peeling stress is generated in the vertical conduction sealing material 19. Due to the peeling stress of the vertical conduction sealing material 19, poor conduction is likely to occur between the conductive particles contained in the vertical conduction sealing material 19, the electrode 13, and the counter electrode 14.

[0037] In general, it is known that the maximum deflection amount when a uniformly distributed load acts is proportional to the fourth power of the side length. That is, as the cell size A decreases, the maximum deflection amount decreases. At this time, the pressure in the power generation element increases and the peeling stress of the upper and lower conduction sealing material 19 increases. Conversely, as the cell size A increases, the maximum deflection amounts of the first substrate 11 and the second substrate increase. At this time, the pressure in the power generation element decreases and the peeling stress of the upper and lower conduction sealing material 19 is suppressed. Therefore, it is expected that the conduction failure between the conductive particles contained in the upper and lower conduction sealing material 19, the electrode 13, and the counter electrode 14 will decrease.

[0038] FIG. 9 is a diagram showing the measurement results of the collapse of the upper and lower conduction sealing material 19 after an 85° C. 85% RH reliability test for dye-sensitized solar cells having various cell sizes A. In the test, dye-sensitized solar cells were fabricated under the conditions of various cell sizes A and cell size B with a seal width of 1 mm (the width of the upper and lower conduction sealing material 19 along the current direction of the power generation element), and the collapse of the conductive particles was measured when each dye-sensitized solar cell was exposed to the conditions of a temperature of 85° C. and a relative humidity of 85%. In the embodiment, the collapse of the conductive particles is measured as the particle size ratio of the conductive particles contained in the upper and lower conduction sealing material 19 to the gap amount of the upper and lower conduction sealing material 19, that is, the interval between the first substrate 11 and the second substrate 12. When this particle size ratio is 1 or less, it means that the conductive particles are collapsed. The occurrence of collapse in the conductive particles means that the conductive particles are pressed by the electrode 13 and the counter electrode 14, and there is a high possibility that conduction is taken between the conductive particles, the electrode 13, and the counter electrode 14.

[0039] Also, in FIG. 9, the cell size A is 4 mm, 5 mm, and 6 mm. The cell size B is 12 mm, 10 mm, and 8.3 mm. The power generation elements with a cell size A of 4 mm and a cell size B of 12 mm, a cell size A of 5 mm and a cell size B of 10 mm, and a cell size A of 6 mm and a cell size B of 8.3 mm are power generation elements with substantially the same cell area.

[0040] As shown in Fig. 9, when the cell size A is 4 mm and 5 mm, the particle size ratio exceeds 1 regardless of whether the cell size B is 12 mm, 10 mm, or 8.3 mm. That is, the conductive particles contained in the upper and lower conduction sealing material 19 are not crushed, and a conduction failure is likely to occur between the conductive particles, the electrode 13, and the counter electrode 14. On the other hand, when the cell size A is 6 mm, the particle size ratio is 1 or less regardless of whether the cell size B is 12 mm, 10 mm, or 8.3 mm. That is, the conductive particles contained in the upper and lower conduction sealing material 19 are crushed, and a conduction failure is less likely to occur between the conductive particles, the electrode 13, and the counter electrode 14.

[0041] Fig. 10 is a diagram showing the measurement results of the peeling rate of the upper and lower conduction sealing material 19 after an 85°C 85% RH reliability test for dye-sensitized solar cells having various cell sizes A. In the test, dye-sensitized solar cells were fabricated under conditions of various cell sizes A and cell sizes B with a seal width of 1 mm, and the peeling rate of the upper and lower conduction sealing material 19 when each dye-sensitized solar cell was exposed to conditions of a temperature of 85°C and a relative humidity of 85% was measured. In the embodiment, the peeling rate of the upper and lower conduction sealing material 19 is measured as the ratio of the area of a portion where significant peeling is visually confirmed to the entire cross-sectional area in a cross-section obtained by cutting the upper and lower conduction sealing material 19 along the seal width direction.

[0042] Also, similar to Fig. 9, in Fig. 10, the cell size A is 4 mm, 5 mm, and 6 mm. The cell size B is 12 mm, 10 mm, and 8.3 mm. The power generation elements with a cell size A of 4 mm and a cell size B of 12 mm, a cell size A of 5 mm and a cell size B of 10 mm, and a cell size A of 6 mm and a cell size B of 8.3 mm are power generation elements with substantially the same cell area.

[0043] As shown in Fig. 10, when the cell size A is 4 mm and the cell size B is 12 mm, the peeling rate of the vertical conduction sealing material 19 is approximately 40%. On the other hand, under the same conditions for cell size B, when cell size A becomes 5 mm, the peeling rate of the vertical conduction sealing material 19 decreases to approximately 20%, which is almost half, and when cell size A becomes 6 mm, the peeling rate of the vertical conduction sealing material 19 decreases to approximately 17.5%. When cell size A is 6 mm, regardless of whether cell size B is 12 mm, 10 mm, or 8.3 mm, the peeling rate of the vertical conduction sealing material 19 is 20% or less.

[0044] Fig. 11 is a diagram showing a comparison of the peeling rates for power generation elements with approximately the same cell area. The horizontal axis in Fig. 11 is the aspect ratio A / B. The vertical axis in Fig. 11 is the peeling rate of the vertical conduction sealing material 19. In Fig. 11, among the peeling rates shown in Fig. 10, the peeling rate when cell size A is 4 mm and cell size B is 12 mm, the peeling rate when cell size A is 5 mm and cell size B is 10 mm, and the peeling rate when cell size A is 6 mm and cell size B is 8.3 mm are plotted respectively. As shown in Fig. 11, it can be seen that under the condition of the same cell area, the larger the cell size A, that is, the larger the value of A / B, the smaller the peeling rate of the vertical conduction sealing material 19.

[0045] From the above, it can be seen that in order to reduce the peeling rate of the vertical conduction sealing material 19 and generate crushing of the conductive particles contained in the vertical conduction sealing material 19, it is desirable that cell size A is 6 mm or more. From the perspective of maintaining the fill factor described above, it is desirable that cell size A is 10 mm or less. Therefore, it is desirable that cell size A is set in the range of 6 mm - 10 mm.

[0046] Actually, the peeling rate of the vertical conduction sealing material 19 is also affected by the seal width. Therefore, when considering the influence of the seal width, if cell size A is A and the seal width is Ws, it is more desirable that the range of A / Ws is 6 - 10.

[0047] As described above, in the embodiment, the cell size A, which is the size in the current direction of the power generation element, is set between 6 mm and 10 mm. More preferably, the cell size A and the seal width Ws are set so that A / Ws is in the range of 6 to 10. Thereby, a dye-sensitized solar cell having a high fill factor and particularly having durability at high temperatures can be obtained.

[0048] The present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the gist thereof at the implementation stage. Also, each embodiment may be implemented in appropriate combination, and in that case, the combined effects can be obtained. Furthermore, the above-described embodiment includes various inventions, and various inventions can be extracted by combinations selected from a plurality of disclosed constituent elements. For example, even if some constituent elements are deleted from all the constituent elements shown in the embodiment, if the problem can be solved and the effect can be obtained, the configuration from which these constituent elements are deleted can be extracted as an invention.

Explanation of Signs

[0049] 1 Dye-sensitized solar cell, 11 First substrate, 12 Second substrate, 13 Electrode, 14 Counter electrode, 15 Electron transport layer, 16 Light absorption layer, 16a Dye, 16b Electron collector, 17 Catalyst layer, 18 Electrolyte, 19 Upper and lower conduction sealant, 20 External sealant.

Claims

1. An electrode formed on a first substrate, An electron transport layer formed on the electrode, A light absorption layer formed on the electron transport layer and containing an electron scavenger and a dye, A counter electrode formed on a second substrate disposed opposite to the first substrate, A catalyst layer formed on the counter electrode, An electrolytic solution filled between the light absorption layer and the catalyst layer, A sealing material interposed between the first substrate and the second substrate and sealing the electrode, the electron transport layer, the light absorption layer, the counter electrode, the catalyst layer, and the electrolytic solution, Comprising a plurality of units of a dye-sensitized solar cell, The region surrounded by the inner wall of the sealing material of each of the units constitutes one power generation element, The size in the current direction of each of the power generation elements flowing through the unit is 6 mm or more and 10 mm or less, A dye-sensitized solar cell.

2. The ratio of the width of the sealing material in the current direction to the size of the current direction is 6 or more and 10 or less, A method for manufacturing the dye-sensitized solar cell according to Claim 1.

3. The sealing material contains conductive particles, The ratio of the particle size of the conductive particles to the distance between the first substrate and the second substrate is 1 or less, The dye-sensitized solar cell according to Claim 1.

Citation Information

Patent Citations

  • dye-sensitized solar cells

    JP7071767B1